Митрополит Андрей Шептицький та Національний музей у Львові - Гентош, Л. (Краєзнавство, 2016)
У статті проаналізована меценатська діяльність митрополита Української греко-католицької церкви А. Шептицького на прикладі його підтримки заснування та діяльності Національного музею у Львові. Фінансова та організаційна підтримка митрополитом Національного
музею розглянута в пов'язанні з його світоглядними засадами та поглядами на місце та роль
Греко-католицької церкви, а також з його душпастирськими обов'язками. В статье проанализирована филантропическая деятельность митрополита Украинской
греко-католичеcкой церкви А. Шептицкого на примере основания им Национального музея во
Львове. Его финансовая поддержка Национального музея пребывала в тесной связи с его взглядами на место и роль Греко-католической церкви, а также с его душпастирской деятельностью. In this articlethe philantropic activity of Greek-Catholic Metropolitan Andrei Sheptyts’kyi has been
analized while focusing on his founding of and patronising to National museum in Lviv. Sheptyts’kyi’s
patronising to the National museum in Lviv was seriously influenced by his ideas and viewpoints
about the role and place of Greek-Catholic Church as well as by his episcopal responsibilities. Metropolitan
Sheptytskyi developed the idea of the importance of national culture and national traditions
for his church. From the early twentieth century onwards he was very much involved in turning his
church into a Ukrainian national institution.
The article explained how the plan to establishe the National museum evolved and which priorities
were chosen by metropolitan and museum’s director Dr. Ilarion Sventsitskyi. Sheptytskyi paid special
attention to sacral art, and spared no efforts in collecting and preservation of sacral atifacts. Icons
were regarded as an important part of the Ukrainian artistic heritage, and thanks to the metropolitan’s
special care they experienced a rebirth.
In the article the financial side of the museum’s existence is described as well. Metropolitan Sheptytskyi
from the moment of museum’s foundation remained the principal and sometimes the unique
source of financial support. He covered the costs of acquisition and restoration of artifacts, but also
research work, and publication of the museum’s academic journal. Sheptytskyi considered National
museum to be the most important institution for cultural development of Ukrainian people and National
museum became the most important part of Metropolitan’s heritage.